Lung cancer in lung transplantation: incidence and outcome. Issue 1107 (4th August 2017) - Pérez-Callejo, David; Torrente, María; Parejo, Consuelo; Laporta, Rosalia; Ussetti, Piedad; Provencio, Mariano
Abstract: Introduction: Malignancies are one of the causes of mortality after lung transplantation. However, little is known about lung cancer outcome after lung transplantation. Methods: We performed a retrospective search of the lung transplantation database at our institution to identify patients diagnosed with lung cancer after lung transplantation. Results: Out of 633 lung transplant patients, lung cancer was detected in 23 of them (3.63%). The most common causes for transplantation were idiopathic pulmonary fibrosis (47.8%) and emphysema (43.4%). A total of 18 patients were diagnosed during follow-up, 12 cases in the native lung (52.2%) and 6 cases in the donor lung (26.1%). The diagnosis was evidenced in the explanted lung in five patients (21.7%). The median of time from transplantation to cancer diagnosis was 39.7 months (24.356.6). Lung cancer was the cause of death in 16 patients. Survival rate at1year from diagnosis of lung cancer was 45.64% (95% CI 0.2431 to 0.6473). Conclusions: Lung transplant recipients constitute a high-risk group for developing lung cancer. Among our patients, lung cancer was predominantly diagnosed in the native lung and at an advanced stage. The primary tumour was the main cause of death in most of these patients.